2016
DOI: 10.1007/s12262-016-1474-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome of Living Donor Liver Transplantation for Hepatocellular Carcinoma

Abstract: The aim of this work is to study the different factors that affect the outcome of living donor liver transplantation for patients with hepatocellular carcinoma (HCC). Between April 2003 to November 2014, 62 patients with liver cirrhosis and HCC underwent living donor liver transplantation (LDLT) in the National Liver Institute, Menoufia University, Egypt. The preoperative, operative, and postoperative data were analyzed. After studying the pathology of explanted liver; 44 (71 %) patients were within the Milan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The 7 tumor related factors, especially lymph node involvement, vascular invasion, and poor tumor differentiation, were significantly related to survival, with large hazard ratios and correspondingly large effects on life expectancy. These findings mirror those of Worns et al 28 Zakaria et al, 4 and Mergental et al 3…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The 7 tumor related factors, especially lymph node involvement, vascular invasion, and poor tumor differentiation, were significantly related to survival, with large hazard ratios and correspondingly large effects on life expectancy. These findings mirror those of Worns et al 28 Zakaria et al, 4 and Mergental et al 3…”
Section: Discussionsupporting
confidence: 86%
“…Two more recent studies bear mention. Zakaria et al 4 reported 1- and 5-year rates of 89% and 67% in 62 Egyptian patients transplanted in 2003 to 2014, with average age 49, and Mehta et al 5 reported 95% and 80% in 187 California patients of median age 58. Comparisons of this type are admittedly tentative, however, as they are may be confounded by differences in ( a ) era of transplant, ( b ) age and other demographics, ( c ) medical and tumor-related risk factors, and ( d ) various study selection criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver transplant (LT) has progressed in the past century from a life‐saving operation with a high morbidity and mortality to a standardized procedure with high success rate and reported 1‐year survival rate of more than 90%. However, surgical complications, such as biliary complications and incisional hernia (IH), are common with this complex procedure 1‐3 …”
Section: Introductionmentioning
confidence: 99%
“…IH forms not only an aesthetic problem, but they may also reduce the quality of life and can lead to serious morbidity due to incarceration or strangulation. Therefore, the prevention of this late complication has become increasingly important 3‐5 …”
Section: Introductionmentioning
confidence: 99%